Occupational choice across generations - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2003)
There are few studies on occupational choices in Germany, and the second generation occupational choice and mobility is even less investigated. Such research is important because occupations determine success in the labor market. In a country like Germany occupations also reflect a general socio-economic standing. This paper looks at the patterns of employment in Germany, analyzes how individual men and women access jobs given their family background, and investigates why men and women have different occupational distributions. Based on the German Socio-Economic Panel we estimate multinomial logit models of occupational choice for the children of immigrants as well as for the natives. Our findings are surprisingly similar for both natives and immigrants. For both Germans and immigrants, we find that gender significantly and differentially affects occupational choice, and that individuals with more education choose higher ranking jobs. The role of experience is important for natives and qualified individuals only. Germans are more likely to choose occupations similar to their fathers? occupation when their father is in the white collar or professional category. In stark contrast, the immigrants? occupational choice is more influenced by their mother?s education and not by their fathers? occupation.
Keywords: J62; J61; J24; F22; D90; 330; occupational choice; intergenerational issues; human capital; migration; Berufswahl; Generationenbeziehungen; Familiensoziologie; Migranten; Ausländische Arbeitskräfte; Schätzung; Deutschland